Mobile phone distance from head and temperature changes of radio frequency waves on brain tissue - Farhad Forouharmajd; Hossein Ebrahimi; Siamak Pourabdian (International Journal of Preventive Medicine, 2018)
Background: Analyzing the possible negative effects of using cell phones on the users' health is an important and vital affair due to rapid growth and extensive use of these devices on human communications and interactions. The aim of this study was to determine the effect of increasing the distance of cell phones to brain tissue on the temperature of the central and gray matters of brain due to the heat generated by radio frequency waves. Methods: This study was an experimental study. A cow's brain tissue was analyzed in a compartment with three thicknesses of 2, 12, and 22 mm, in the distances of 4 mm and 4 cm from a cell phone for 15 min. Lutron thermometer was used to measure the tissue temperature, and the data analysis were done by Lutron and MATLAB software packages. Results: The tissue temperature was increased while confronting with a cell phone in distances of 4 mm and 4 cm in all the three thicknesses of 2, 12, and 22 mm. The tissue temperature was higher after removing the confrontation at 4 mm distance as compared to the distance of 4 cm. Conclusions: During confrontation and after that with the cell phone, reducing the distance of brain tissue and the cell phone increased the tissue temperature intensely. In fact, by increasing the cell phone distance from brain tissue, the thermal effect of radiofrequency waves was reduced.